The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/01973533.2013.785399
|View full text |Cite
|
Sign up to set email alerts
|

Reaching for the (Product) Stars: Measuring Recognition and Approach Speed to Get Insights Into Consumer Choice

Abstract: In three studies, an easy-to-apply response time task that differentiates between recognition and approach speed was applied. The results indicate that individuals recognized and approached positive stimuli faster than negative stimuli (Pilot Study). But, when the choice options differed less in valence, approach movement time was a better predictor of consumer choice and willingness to pay than recognition time (Study 1) and a better predictor of consumer choice than self-reports when the choice was made with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 62 publications
(107 reference statements)
3
15
2
Order By: Relevance
“…After signing a statement of agreement, participants completed the RaBAT (Genschow et al, 2013), indicated basic demographic characteristics, and were then debriefed, thanked, and dismissed.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After signing a statement of agreement, participants completed the RaBAT (Genschow et al, 2013), indicated basic demographic characteristics, and were then debriefed, thanked, and dismissed.…”
Section: Methodsmentioning
confidence: 99%
“…A more elegant test of the theoretical assumption that threatening stimuli lead to fast recognition and slow approach responses would involve the assessment of recognition and approach latencies within the same response sequence. As described before, the RaBAT (Genschow et al, 2013) allows doing this in a most convenient manner.…”
Section: Responses Toward Threatening Stimulimentioning
confidence: 99%
See 3 more Smart Citations